The Conceptual Politics of Democracy Promotion. - Hobson, Christopher (Democratization studies., 2011)
How do different meanings of the concept of 'democracy' operate in democracy promotion? How do conceptual decisions influence real political events? How is policy and reflection on democracy promotion shaped by the way different practitioners and scholars understand democracy? The Conceptual Politics of Democracy Promotion explores the way in which the meaning, content and context of 'democracy' are interpreted by different actors in democracy promotion, and how these influence political decisions. Introducing a theoretically new approach to the study of democracy promotion, the volume shows h.